Synthesis and conformational analysis of His-Phe-Arg-Trp-NH2 and analogues with antifungal properties - Masman, Marcelo Fabricio (2006)
The synthesis, in vitro evaluation, and conformational study of His-Phe-Arg-Trp-NH2 and related derivatives acting as antifungal agents are reported. Among them, His-Phe-Arg-Trp-NH2 and His-Tyr-Arg-Trp-NH2 exhibited antifungal activity against Cryptococcus neoformans. Antifungal activity of these compounds appears to be closely related to the α-MSH effect. A conformational and electronic study allows us to propose a biologically relevant conformation for these tetrapeptides acting as antifungal agents. In addition, these theoretical calculations permit us to determine the minimal structural requirements to produce the antifungal response and may provide a guide for the design of compounds with this biological activity.